Fabrication of Sensitive Potentiometric Cholesterol Biosensor Based on Co3O4 Interconnected Nanowires. Issue 9 (24th July 2014) - Ibupoto, Zafar Hussain; Elhag, Sami; Nur, Omer; Willander, Magnus
Abstract Highly sensitive, selective, reliable and inexpensive cholesterol biosensors are highly demanded for the routine monitoring of cholesterol molecules in order to prevent heart failure incidents. In this study, Co3O4 nanostructures are synthesized using polyvinyl pyrrolidone surfactant as growth template by a low temperature aqueous chemical growth method. The morphology of nanostructures was investigated by scanning electron microscopy and X‐ray diffraction techniques. The nanostructures exhibit interconnected nanowires like morphology with interconnected network of nanowires. The nanostructures of Co3O4 are polycrystalline. The cholesterol oxidase was physically adsorbed on the interconnected nanowires of Co3O4 for the chemical sensing of cholesterol molecules. The sensor device detected a wide range of cholesterol from 1×10−7 M to 1×10−3 M concentrations with sensitivity of −94.031 mV/decade. A detection limit of 0.035×10−7 M cholesterol concentration was observed and a fast response time of 10 s was also noticed. The fabricated device is highly stable, selective, sensitive, reproducible and repeatable. All the collected information about presented cholesterol biosensor indicates its potential application for the monitoring of cholesterol concentrations from human blood serum and real‐life samples.